Topical Drug Delivery in the Treatment of Skin Wounds and Ocular Trauma Using the Platform Wound Device - Elof Eriksson; Gina L Griffith; Kristo Nuutila (MDPI AG, 2023)
Topical treatment of injuries such as skin wounds and ocular trauma is the favored route of administration. Local drug delivery systems can be applied directly to the injured area, and their properties for releasing therapeutics can be tailored. Topical treatment also reduces the risk of adverse systemic effects while providing very high therapeutic concentrations at the target site. This review article highlights the Platform Wound Device (PWD) (Applied Tissue Technologies LLC, Hingham, MA, USA) for topical drug delivery in the treatment of skin wounds and eye injuries. The PWD is a unique, single-component, impermeable, polyurethane dressing that can be applied immediately after injury to provide a protective dressing and a tool for precise topical delivery of drugs such as analgesics and antibiotics. The use of the PWD as a topical drug delivery platform has been extensively validated in the treatment of skin and eye injuries. The purpose of this article is to summarize the findings from these preclinical and clinical studies.